P-799 To evaluate the effect of Intra-ovarian platelet rich plasma instillation on the clinical outcome of women with diminished ovarian reserve: A prospective interventional study. (30th June 2022) - Patel, G; Singh, N; Malhotra, N; Mahey, R; Saini, M; Sethi, A
Abstract: Study question: Does intra-ovarian instillation of platelet rich plasma (PRP) improves the clinical outcome of IVF cycles in women with Diminished Ovarian reserve (DOR)? Summary answer: PRP instillation leads to consistent improvement in Antral follicle count (AFC), thus achieving clinical pregnancy rate of 33.3% per cycle in women with DOR. What is known already: There is rising incidence of females with diminished ovarian reserve (DOR) especially among Asian ethnicity. With the emergence of regenerative medicine, multiple studies have evaluated the role of intra-ovarian PRP, demonstrating a beneficial role in improving ovarian reserve parameters (serum Follicular stimulating hormone (FSH), serum anti-Mullerian hormone (AMH), AFC). Despite its' favorable effects on biochemical markers and AFC, data regarding improvement in clinical outcome remains elusive and led to inception of this study. Study design, size, duration: A prospective interventional study was conducted at Division of Reproductive Medicine of a tertiary care institute. 41 infertile females aged 20-39 years with DOR (AMH <1.2 ng /ml; AFC<5) were enrolled in the study during a 6-month period beginning from August 2021. Participants/materials, setting, methods: After informed consent, patients received fresh autologous PRP, prepared from 30 ml venous blood. 1.5ml of PRP instilled in each ovarian stroma between day 7-10 of menstrual cycle under sedation. Patients were followed up for three-consecutive months to assess ovarian reserve parameters including serum FSH, AMH and AFC. Patients showing significant improvement in parameters were recruited for fresh IVF cycles using Antagonist protocol with 1% transdermal testosterone. Outcomes were analysed using linear mix effect model. Main results and the role of chance: The average platelet concentration in PRP was ∼10, 00, 000 platelets/µL. The mean age of enrolled patients was 31.22±4.16 years. Linear improvement in AFC (3.63 vs 6.98 vs 7.97 vs 6.90, p <0.001) was observed from baseline to three consecutive follow-up months with maximal response witnessed in second month in 57.1% of those undergoing IVF cycle. However, there was no significant difference in Serum FSH ( p =0.11) and AMH ( p =0.16) from the baseline post intervention. Of the 41 patients, 35 (85.3%) responded to the treatment and underwent IVF antagonist cycle. 5 out of 35 IVF cycles were cancelled mid-cycle due to poor ovarian response. The mean dose of gonadotropin requirement was 2667.5±281.1 IU (Follicular stimulating hormone) and 1400±337.3 IU (Human menopausal gonadotropin). The average number of oocytes retrieved was 5.7±2.2 whereas mean number of MII oocytes was 4.63±1.85. The fertilization rate and the cleavage rate were 92.4% and 74.1% respectively. Of the thirty patients, eight patients underwent day 2 transfer due to poor grade of embryos. Mean number of grade 1- day 3 embryos was 1.25±0.55 with surplus embryos available for cryopreservation in 14 patients. The overall clinical pregnancy rate per transfer was 33.33%. No adverse events were reported. Limitations, reasons for caution: This was a prospective single arm study. A randomized controlled trial comprising a "no-treatment" arm would establish a Level-I evidence. However, "no-treatment" arm in a developing country like ours, imposes financial burden on the couple with no guaranteed clinical success and thus raising ethical concern and need for ovarian rejuvenation. Wider implications of the findings: With the impetus to provide a biological child to these DOR women, intra-ovarian PRP instillation as a method of ovarian rejuvenation holds promising results. Evidently, PRP is not only effective in improving ovarian reserve but this translates into an improved reproductive outcome in a population, previously limited to oocyte donation. Trial registration number: REF/2022/01/051033